Implementation of the Science Curriculum at SDN Beringin 1 Dasuk - Imelda Prastika; Dwi Putri Malinda; Isma Apriliana Putri Latifa; Aulina Prayoga; Wildanul Hakim (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in Natural and Social Sciences (IPAS) learning at SDN Beringin 1 Dasuk. Using a descriptive qualitative approach, this research involved fourth-grade IPAS teachers, school principals, and students as research subjects. Data were collected through participatory observation, in-depth interviews, and documentation. The results showed that learning planning has been well-prepared according to the components of the Merdeka curriculum teaching modules, covering three competency dimensions: cognitive, psychomotor, and affective. Scientific learning strategies and inquiry learning models proved effective in increasing active involvement and student learning outcomes through observing, questioning, collecting information, associating, and communicating stages. However, implementation still faces significant challenges including imbalanced achievement of three competency dimensions with cognitive aspect dominance, paradigm shift from teacher-centered to student-centered, time constraints and classroom management issues, and limited practical facilities. Implementation success heavily depends on teacher competence in mastering innovative learning methods and designing contextual learning. This study recommends continuous teacher competency development, adequate infrastructure provision, and comprehensive support from all parties to optimize science literacy development and 21st-century competencies of students.